Pengembangan Game Slayer Angel Dalam Mengikuti Studi Independen Kampus Merdeka Di PT. Agate Internasional - Syalman Hakim (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2022)
Games are one of the entertainment media that are the choice of almost everyone to get rid of boredom or fill spare time, there are also games that are used as hobbies and moreover games are now used as electronic sports (e-sports). Currently, the game has many types of games, one of which is the type of idle RPG game. Idle game is a game concept that can play itself without us having to play it, while RPG game stands for Role-Playing Game is a game where players play the role of a character. So idle RPG is a combination of two game genres, namely idle games and RPG games. In this study, researchers used the MDLC (Multimedia Development Life Cycle) method, which is suitable for designing and developing a media application which is a combination of image, sound, and video media. The MDLC method has six stages including Concept, Design, Material Collecting, Assembly, Testing, and Distribution. The results of this study are in the form of an idle RPG genre game that is applied to mobile android.